The color of family history, race, and the politics of ancestry - O'Malley, Michael (The University of Chicago Press, 2024)
"For endless decades, white American authorities sought to police racial boundaries and define racial identities. But that dubious enterprise was subject not just to human error but to changing concepts of race. Thus was Michael O'Malley, a descendant of a Philadelphia Irish-American family, came to have "colored" ancestors in Virginia. The meanings of the names and relationships in the official record kept shifting in confusing and unexpected ways. O'Malley teases out how those changes affected his ancestors as they navigated what it meant to be "white," "colored," "mixed race," or anything else in America from the nineteenth century onward-even today, when digitization and privatization are changing how such racecraft manifests"--
Keywords: Families / United States / History; Irish American families / United States / History; Multiracial families / United States / History; Race awareness / United States; Multiracial people / Race identity / United States; Irish Americans / United States / Genealogy; Genealogy / Political aspects / United States; Identity politics / United States; United States / Genealogy; Familles / États-Unis / Histoire; Familles métissées / États-Unis / Histoire; Conscience de race / États-Unis; Politique identitaire / États-Unis; Familles américaines d'origine irlandaise / États-Unis / Histoire; REFERENCE / Genealogy & Heraldry